Faktor-Faktor yang Berpengaruh terhadap Pernikahan Usia Dini - Erni Riany; Riska Yanuarti; Bintang Agustina Pratiwi; Wulan Angraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the factors that influence early marriage in Air Rami District, Mukomuko Regency. This research method is a quantitative study with a cross-sectional study approach. The results showed that the factors that influence early marriage in Air Rami District, Mukomuko Regency include knowledge (p = 0.000), attitude (p = 0.004), parents' income (p = 0.001), exposure to information media (p = 0.901), the influence of peers (p = 0.569), the role of parents (p = 0.000), the number of family members (p = 0.039), while the factor that did not affect early marriage in Air Rami District, Mukomuko Regency was exposure to information media (p = 0.901), peer influence (p = 0.569), and culture (p = 0.104). In conclusion, there is an influence between knowledge, attitudes, parents' income, parents' role, and family members in early marriage. Meanwhile, what did not affect early marriage was exposure to information media, peer influence, culture. Keywords: Marriage, Early Age